The factors influencing niche consumers’ behavior in the brewery market in Poland - Rywocki, Karol (Journal of Education, Health and Sport, 2021)
The aim of this article is to present the main factors influencing the behavior of consumers of the niche products of brewery market in Poland. On the basis of the conducted research – via direct survey, the author tries to determine the reasons why they purchase niche beers. Where do they find the information about niche products? How often and on what occasion do consumers drink niche beer? What interests and what standards concerning healthy lifestyle do they have? The author also defines and classifies niche producers on the brewery market in Poland.